INTEGRATION OF NUDGING-BASED KANSEI ENGINEERING AND HUMAN-CENTERED DESIGN: A CONCEPTUAL FRAMEWORK IN HEALTHCARE SERVICE - Hartono, Markus (JEMIS (Journal of Engineering & Management in Industrial System), 2025)
This study presents a conceptual framework for the modification of Kansei Engineering (KE), incorporating nudging-enabled features with human-centered design (represented by Design Thinking (DT) methodology) principles applied in healthcare services. Kansei Engineering (KE) and Nudge Theory (NT) have a similar goal of influencing and directing users’ behavior and intentions based on the fulfillment of their critical needs. KE focuses on translating customer emotional needs into design parameters, whereas NT stresses changing customer behavior using indirect instructions and positive reinforcements. Once emotional satisfaction is obtained, it is hoped that positive behavior will be promoted. Addressing customers' emotional demands combined with nudge-based features in patients’s healthcare service experiences is a strategic necessity that can result in considerable commercial benefits. Healthcare that creates positive emotional connections can improve patient happiness, inspire loyalty, and build a strong, differentiated brand in a competitive environment. More importantly, it may boost patient recovery rates and promote more sustainability practices in hospitals or healthcare domains for a long-term period. Hence, this study introduces a novel integrated framework that combines KE, NT, and DT to align emotional satisfaction with behavioral outcomes in healthcare service design, particularly in developing emotionally and behaviorally supportive strategies for non-critical patient care.